Changes in the Islamic Banking Industry Pre and Post the Financial Crisis - Al Suwaidi, Abdulla Khalid (2015)
The banking, investment and lending practices adopted by Islamic banks have recently drawn the attention of many researchers and professionals. This is especially after it emerged that these financial institutions that apply the Islamic banking model performed better during the recent global financial crisis in 2008 as compared to their counterparts that employ the conventional banking practices. Islamic banking is a banking system that operates according to Sharia’h laws, which prohibit charging or receiving interests, or investing in products and derivatives that are prohibited in Islam. Instead, the laws encourage profit and loss sharing rather than transfer of risks. The banks provide a number of financial products in different modes that resemble many products in conventional banking. The Islamic banks did relatively well in comparison to their conventional counterparts during the financial crisis. The performance could be largely attributed to the banking system that discourages market speculation and unnecessary risks while advocating for simple financial transactions based on mutual gains from real economic activities. Besides its apparent resilience during the global financial crisis, the Islamic banking model has been associated with the positive economic growth observed in the economies of Malaysia and United Arabs Emirates in the past three decades. There is a necessity for financial institutions, business institutions, regulatory authorities and consumers to look into specific strategies that would constitute desirable features for a stable and effective financial system. The current research sought to trace the development and rationale of the Islamic Banking model as well as identify the most significant and unique characteristics that have facilitated the resilience of the Islamic Banking sector to economic shocks during the recent global recession. Although Islamic banks performed significantly better in the global financial crisis, they were later significantly affected by the depression that hit the real economy for many countries. Certain lending practices and investment management guidelines following Islamic banking principles emerge as being desirable for improving the resilience and effectiveness of commercial banks for sustained economic growth and stability.